Luteolysis and pregnancy outcomes after change in dose delivery of prostaglandin F2α in a 5-day timed artificial insemination program in dairy cows - Jeffrey S. Stevenson; Stephanie Leeann Pulley; Scott L. Hill (Kansas Agricultural Experiment Station Research Reports, 2014)
Three experiments were conducted to determine if a larger dose of prostaglandin F2α (PG) administered on day 6 of a 5-day Ovsynch timed artificial insemination (AI) program would induce regression of the corpus luteum to facilitate AI and pregnancy outcomes similar to a traditional 5-day program with two doses of PG. When applying a 5-day program, cows that ovulate in response to the first GnRH injection have a new corpus luteum (CL) that is 2 days younger when PG is administered in a 5- versus 7-day program. To regress successfully the younger CL, a second injection of PG must be given 24 hours after the first PG injection to prevent reduced pregnancy rate after the timed AI. These experiments demonstrated that administering 50 mg PG (10 mL Lutalyse) on day 6 produced luteolysis as efficiently as 25 mg PG (5 mL Lutalyse) administered on days 5 and 6 when the cut point for progesterone was 1 ng/mL 72 hours after the first PG injection or 48 hours after the larger PG dose. In contrast, when the cut point was 0.5 ng/mL, the larger dose of PG was less effective. Pregnancy outcomes in cows did not differ between treatment doses except in one herd (Exp. 3). Although pregnancy outcomes were reduced only in one herd with the larger PG dose, this difference may be confounded with the earlier injection of the second GnRH injection 16 hours before timed AI, rather than failure of luteolysis in response to the larger dose of PG. Delaying the timing of AI, injection of the second GnRH, or both may be warranted to allow sufficient time for progesterone to decrease to basal concentrations in response to a larger dose of PG on day 6 to prevent a reduction in fertility.; Dairy Day, 2014, Kansas State University, Manhattan, KS, 2014; Dairy Research, 2014 is known as Dairy Day, 2014
Keywords: Dairy Day; 2014; Kansas Agricultural Experiment Station contribution; no. 15-156-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 1111; Luteal tissue; Luteolysis; Ovulation; Progesterone; Pregnancy rate